Hydrogenative Cyclopropanation and Hydrogenative Metathesis. (17th May 2019) - Peil, Sebastian; Guthertz, Alexandre; Biberger, Tobias; Fürstner, Alois
Abstract: The unusual geminal hydrogenation of a propargyl alcohol derivative with [Cp X RuCl] as the catalyst entails formation of pianostool ruthenium carbenes in the first place; these reactive intermediates can be intercepted with tethered alkenes to give either cyclopropanes or cyclic olefins as the result of a formal metathesis event. The course of the reaction is critically dependent on the substitution pattern of the alkene trap. Abstract : Janus‐Charakter : Die gem ‐Hydrierung von Propargylalkoholen ermöglicht einen konzeptionell neuartigen Zugang zu Metallcarbenkomplexen. So führt die Verwendung von [Cp*RuCl]4 als Katalysator zu Pianostool‐Rutheniumcarbenen, die entweder eine Cyclopropanierung oder eine Ringschluss‐Metathese eingehen; das Ergebnis der Reaktion wird weitgehend vom Substitutionsmuster des olefinischen Reaktionspartners bestimmt.